Propagation of Cannabis sativa (L.) plants through cuttings and use of auxin phytoregulators - Porras-García, Beatriz; Pinzón-Sandoval, Elberth Hernado; Almanza-Merchán, Pedro José (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
Cannabis sativa (L.) is an annual herbaceous species which has been extensively cultivated and used as a medicinal plant and for recreational purposes. Its medicinal value is primarily attributed to a group of secondary metabolites called phytocannabinoids, which are mainly concentrated in the essential oils of unfertilized female flowers. Asexual reproduction allows for the offspring of plant material while maintaining the genetic characteristics of the mother plant. The aim of the research was to improve the vegetative propagation process of Cannabis sativa (L.) cv. Eco-2, which has characteristics of medicinal phytocannabinoid producers, using auxin plant growth regulators (NAA and IBA) at different doses. The study was conducted under greenhouse conditions in the municipality of Pesca (Colombia). Doses of 400, 800 and 1,000 mg L-1 and a control without application were evaluated for plant height, stem diameter, number of branches, root volume and length, and rooting percentage. The best treatment was obtained with the application of NAA at a dose of 800 mg L-1, which resulted in a rooting percentage of 86.6%, a root length and volume of 9.0 cm and 5.0 cm3, and an increase in the length of the cutting by 3.8 cm, with significant differences compared to the treatment without application, after 4 weeks of planting. The use of auxin plant growth regulators becomes an alternative with high potential for the propagation of medicinal cannabinoid-producing plants.